2015
DOI: 10.1590/2317-1782/20152014165
|View full text |Cite
|
Sign up to set email alerts
|

Study of the long-term effects of frequency compression by behavioral verbal tests in adults

Abstract: PURPOSE: To verify the effect of long-term use of hearing aids with frequency compression for verbal behavior tests and daily activities. METHODS: Thirty-two adults, aged between 30 and 60 years old, with moderate to severe sensorineural hearing loss at high frequencies with steeply sloping configuration were divided into two groups: 16 with hearing aids with frequency compression algorithm enabled and 16 not enabled. All participants underwent the detection tests of consonant sounds, monosyllable recognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…These results concur with the researched literature (9,22,23,24,25) . In one study, the use of a frequency transposition algorithm in hearing impaired individuals with presence of dead regions in the cochlea, from 1.5 kHz, was efficient in the identification of the phoneme / ∫ / and, in general, there was no Identification of the other phonemes of the English language.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results concur with the researched literature (9,22,23,24,25) . In one study, the use of a frequency transposition algorithm in hearing impaired individuals with presence of dead regions in the cochlea, from 1.5 kHz, was efficient in the identification of the phoneme / ∫ / and, in general, there was no Identification of the other phonemes of the English language.…”
Section: Discussionsupporting
confidence: 93%
“…In this same study, the authors demonstrated that the applied algorithm was effective to help in the detection of final fricatives / s, z /, when comparing the results obtained with the filtered speech (control) (9) . In Brazil, a recent study demonstrated that frequency compression in adults resulted in improved hearing, detection of phonemes / s, ∫ / and speech recognition, with progressive improvement over 12 months (22) . The present study found results that diverge from the aforementioned literature.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of studies shows that NFC benefits speech intelligibility in hearing-impaired listeners, especially, in the perception of fricatives and affricatives ( Alexander, 2012 ; Alnahwi & AlQudehy, 2015 ; Bohnert, Nyffeler, & Keilmann, 2010 ; Ellis, 2012 ; Glista et al., 2009 ; Glista, Scollie, & Sulkers, 2012 ; Kopun et al., 2012 ; Marchesin & Iorio, 2015 ; McCreery et al., 2013, 2014 ; Nyffeler, 2008 ; Simpson, Hersbach, & McDermott, 2005 , 2006 ; Souza et al, 2013 ; Stender & Groth, 2014 ; Wolfe et al., 2010 , 2011 ).…”
Section: Introductionmentioning
confidence: 99%